Opportunities for heat pumps adoption in existing buildings: real-data analysis and numerical simulation. (October 2017) - Jarre, M.; Noussan, M.; Poggio, A.; Simonetti, M.
Abstract: The space heating of buildings represents one of the most important causes of energy consumption in Europe. The necessity to increase the share of renewable energy within the sector is hindered by the difficulty to renew and refurbish the existing building stock. In this context, heat pumps can have an important role in helping increase the renewable share of thermal energy production for the civil sector, in particular in those countries in which the electricity generation mix has large contributions from renewable energy sources. The paper presents a real-data analysis and a numerical simulation to evaluate the opportunity to substitute traditional heat generation systems (natural gas boilers) with air-source heat pumps or hybrid solutions. Three buildings located in Turin (Italy) are taken as case-study, and the hourly profiles of outdoor temperature, water supply temperature and absorbed thermal power are used to simulate four heat generation scenarios, that are compared in terms of primary energy consumption. Results show that (1) the substitution of the traditional natural gas boiler with a heat pump (with backup electric resistance) is always favorable (18% to 32% of primary energy reduction); (2) the influence of water supply temperature of each building on the overall primary energy saving is very high; (3) the adoption of a hybrid system (heat pump and natural gas boiler working alternatively) provides advantages in terms of reduced primary energy consumption only if the required supply water temperature is high. Further studies will investigate the economic aspects and will introduce comparisons with condensation natural gas boilers.